Pelatihan Tilawati dalam Mengembangkan Bacaan Al-Qur’an Para Peserta Didik Madrasah Ibtidaiyah - Muharam, Abdillah; Wulandari, Hayani (Jurnal Pengabdian Masyarakat PGSD, 2023)
The issue that arises in this study is the lack of ability to read the Qur’an with beautiful rhythms and good reading according to the rules of tajwid science. Therefore, the presence of the Tilawati Method is a recent innovation in reading the Qur’an. This training has many advantages, in which the Tilawati method is an approach to learning the Qur’an that combines habituation through a classical approach with reading and listening techniques. There are various learning resources. This training can be applied by various circles. This community service is carried out by targeting class V students at MI Mansya'ul Huda. The method used in writing this article involves certain stages: 1) preparation, which includes gathering training needs, determining activity materials and participants, and providing materials and teaching aids, 2) implementation, which includes tests to measure reading ability levels, and 3) evaluation. The results of this training show the development of students in reading the Qur’an in accordance with the rules of the science of recitation and beautiful rhythms. Concrete evidence has shown that this Tilawati training has high effectiveness in increasing and awakening students' enthusiasm for reading the Qur’an.